MODEL SIMULASI UNTUK MENGAMATI PENGARUH TEGANGAN TARIK-SISA SILINDER AUTOFRETTAGE LARAS SENAPAN - Sahlan Sahlan (Sekolah Tinggi Teknik PLN, 2015)
The analysis of autofrettage on fatigue-crack propagation of crack are well documented, that is experimental work shows the effects of positive stress ratio or tensile-minimum stress during thefatigue cycles on the fatigue-crack inition from holes. This simulates model the effect of the residual-tensile stresses at the outside surface of autofrettage cylinders. S-N curves and modifiedGoodman diagrams are shown for fatigue-crack inition. This allows a tremendous advantage in retarding crack initiation and propagation in the early stages of crack growth, wich accounts for thedramatic increases in useful service life for an autofrettage cylinder compared to a nonautofrettaged cylinder.